Low-Complexity Online Synthesis for AMIDAR Processors. (28th December 2010) - Döbrich, Stefan; Hochberger, Christian
Abstract : Future chip technologies will change the way we deal with hardware design. First of all, logic resources will be available in vast amount. Furthermore, engineering specialized designs for particular applications will no longer be the general approach as the nonrecurring expenses will grow tremendously. Reconfigurable logic has often been promoted as a solution to these problems. Today, it can be found in two varieties: field programmable gate arrays or coarse-grained reconfigurable arrays. Using this type of technology typically requires a lot of expert knowledge, which is not sufficiently available. Thus, we believe that online synthesis that takes place during the execution of an application is one way to broaden the applicability of reconfigurable architectures. In this paper, we show that even a relative simplistic synthesis approach with low computational complexity can have a strong impact on the performance of compute intensive applications.